Analysis of the Influence of Tourism Infrastructure Availability on Public Interest in Visiting Loang Baloq Beach - Witha Dharma, Ida Made; Diswandi, Diswandi; Hak, Muhammad Bai'ul (West Science Interdisciplinary Studies, 2025)
This study aims to analyze the influence of the availability of tourism infrastructure on the interest of the community to visit Loang Baloq Beach. The tourism infrastructure referred to includes facilities such as entertainment stages, places of worship, parking areas, playgrounds, and medical posts. The research method used is field research with a quantitative approach, where primary data is collected through the distribution of questionnaires to visitors of Loang Baloq Beach. The results show that tourism infrastructure has a significant impact on visiting interest, where the availability of adequate facilities can enhance visitor comfort and experience. Therefore, the development and improvement of tourism infrastructure at Loang Baloq Beach is expected to increase the attractiveness of the destination and the interest of the community to visit. This study provides important insights for tourism managers in planning and enhancing existing facilities to support the growth of tourism in the area.